PENERAPAN MODEL PEMBELAJARAN PROJECT BASIC LEARNING (PjBL) UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS BERITA KELAS XI MENU 4 SMA NEGERI 1 KUPANG - Tuka, Jemy Arison; Nai, Firmina Angela; Pellondou, Mezra Elisabeth (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
Abstract This study aimed to improve learning outcomes of Class XI students of SMA Negeri 1 Kupang through the application of differentiated product learning. This approach was chosen because it is centered on the students' needs. In the context of student diversity, this study focuses on adapting learning interests to the characteristics of news writing materials. The news writing element is integrated into Bloom's taxonomy at the C6 (creating) level, allowing students to have the freedom to choose the news product they want to produce according to their individual interests. The classroom action research was conducted in two cycles with the same approach, namely Culturally Responsive Teaching (CRT). Although the approach was the same in both cycles, in Cycle I, students were only given the opportunity to write news texts as the product to be produced. In Cycle II, students were given the freedom to choose various forms of news products according to their individual interests. The analysis results show a significant increase in student learning outcomes, with an average score increase from Cycle I (73.42) to Cycle II (90.57), and all students achieved a classical completeness level of 100% in Cycle II. The implications of this study emphasize the importance of professional development to support teachers in effectively applying differentiated product strategies, as well as continuity in improving the quality of sustainable learning in the future. Keyword: interest, differentiated, project, product, Culturally Responsive Teaching.